(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
In an ever-evolving global landscape, contemporary issues are increasingly complex and affect various aspects of human life. Changes in work patterns, digitalization, and rapid urbanization have had a major impact on people’s lifestyles. One of the consequences of these changes is the rise in non-communicable diseases (NCDs), which are now the leading cause of death in many countries. This research focuses on the relationship between modern lifestyles and the increase in NCDs using the literature study method. Data sources in this study include reputable academic journals, official reports of world health organizations, and statistical data from the Indonesian Ministry of Health, with data collection techniques through systematic literature searches, critical evaluation, and comparative analysis of various relevant scientific sources. The results show that unhealthy diets, lack of physical activity, and high levels of stress have significantly contributed to the surge in cases of diabetes, hypertension, and cardiovascular disorders. To address this phenomenon, preventive measures involving health education, promotion of healthy lifestyles, and cross-sectoral cooperation are needed to create a healthier and higher quality environment.